Analyzing marketing mix strategies and personal factors influencing BISI hybrid maize seed purchases: insights from agricultural development in Soppeng District, Indonesia - Rustam, Sulfiana; Darma, Rahim; Jamil, Muhammad Hatta; Tenriawaru, A. Nixia; Fudjaja, Letty; Akzar, Rida; Nawi, Nolila Mohd; Bakheet Ali, Hamed Noralla (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
As a staple food and a key component of livestock feed, the growing demand for maize in Indonesia has spurred the expansion of hybrid maize cultivation. However, despite advancements in seed technology and government initiatives to boost maize production, farmers in rural areas continue to face obstacles in accessing high-quality seeds. This study explores the influence of the marketing mix—encompassing product, price, promotion, and distribution—alongside personal factors on farmers’ purchasing decisions for hybrid maize seeds in Soppeng District. Utilizing structural equation modeling (SEM) and survey data from 100 respondents, the findings indicate that product quality and price are the most critical determinants, with farmers prioritizing seed performance and affordability. Distribution also plays a vital role in rural areas, ensuring that farmers can readily access high-quality seeds. At the same time, personal factors such as farming experience and income significantly shape purchasing behavior. Notably, promotional efforts appear to have a limited impact, suggesting that traditional marketing approaches may not be the most effective in this context. Seed companies should focus on product development, refine pricing strategies, and strengthen distribution networks to enhance market penetration. In parallel, policymakers can facilitate access to agricultural credit, invest in rural infrastructure, and promote farmer education programs to improve purchasing power and awareness. Ultimately, adapting marketing strategies to align with local economic and cultural conditions can drive greater adoption of hybrid seeds, boost agricultural productivity, and contribute to the long-term sustainability of rural farming communities.